The Influence of Technology 4.0 on the Religious Behavior of the Millennial Generation as an Agent of Conservation with an Authentic Learning Model Amidst the Covid 19 Pandemic - A . Kristiadji Rahardjo; Ria Manurung (Universitas Muhammadiyah Enrekang, 2022)
The research aims to analyze influence of technology 4.0 with Authentic Learning model to strengthen foundations of spirituality and morals of integrated millennial generation religious life so that they can act as conservative agents who have an identity in responding to globalization amid the Covid-19 pandemic. The type of research is field research with method of qualitative analysis to obtain data relevant to research topic. Primary data in the study were collected by distributing questionnaires through online media in form of Google forms and offline to respondents. Sampling technique in a non-probability way uses snowball sampling technique. Number of samples is 400 respondents with millennial generation criteria with an age range of 17 to 35 years in Banyumas Regency, consideration that Banyumas Regency is one of student cities in Central Java Province. Based on data from Central Bureau of Statistics for Banyumas Regency, there are 11 tertiary institutions in Purwokerto spread over four sub-districts, namely East Purwokerto, South Purwokerto, West Purwokerto, and North Purwokerto. The test results show that significance value is 0.000 <0.05; thus, it can be concluded that H0 is rejected, and H1 means that there is an influence of Technology 4.0 (X1) on the Religious Behavior of Millennial Generation as an Agent of Conservation (Y). The R Square value from the results of moderating variable regression test shows 0.727 or 72.7%, so it can be concluded that H2 is accepted and H3 is rejected; namely, Authentic Learning variable can strengthen effect of Technology 4.0 variable on Millennial Generation's Religious Life Behavior variable as an Agent of Conservation.